The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1155/2012/732902
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Stress Delays Periodontitis Healing in Rats: The Involvement of Basic Fibroblast Growth Factor

Abstract: Objective. To evaluate the effects of psychological stress on periodontitis healing in rats and the contribution of basic fibroblast growth factor (bFGF) expression to the healing process. Methods. Ninety-six rats were randomly distributed into control group, periodontitis group, and periodontitis plus stress group. Then, the rats were sacrificed at baseline and week(s) 1, 2, and 4. The periodontitis healing condition was assessed, and the expression of interleukin-1β (IL-1β), tumor necrosis factor-α (TNF-α), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 40 publications
(57 reference statements)
0
15
0
Order By: Relevance
“…Proinflammatory cytokines, such as interleukin‐1 and tumor necrosis factor‐alpha, are critical in the early healing events, and thus any stress‐induced alterations may impair wound healing, especially in the early stages. A recent experimental periodontitis study in rats also demonstrated decreased expression of basic fibroblast growth factor and slower recovery of expression of basic fibroblast growth factor in the stress group . Finally, reduced blood flow, as a result of increased catecholamine levels in response to stress, can, in turn, affect oxygen‐dependent healing mechanisms, such as angiogenesis, collagen synthesis and epithelialization .…”
Section: Stressmentioning
confidence: 93%
“…Proinflammatory cytokines, such as interleukin‐1 and tumor necrosis factor‐alpha, are critical in the early healing events, and thus any stress‐induced alterations may impair wound healing, especially in the early stages. A recent experimental periodontitis study in rats also demonstrated decreased expression of basic fibroblast growth factor and slower recovery of expression of basic fibroblast growth factor in the stress group . Finally, reduced blood flow, as a result of increased catecholamine levels in response to stress, can, in turn, affect oxygen‐dependent healing mechanisms, such as angiogenesis, collagen synthesis and epithelialization .…”
Section: Stressmentioning
confidence: 93%
“…These biomarkers include: measuring salivary cortisol levels, standardized stress scales and questionnaires, and the community index of periodontal care needs (CIPC) [18]. From there, studies conducted on animals [19][20][21] and on people, whether it be cohort, cross-sectional, case-control or clinical trials [6,15,28,22] showed a positive correlation between stress and the occurrence of periodontal disease. According to several recent literature reviews, the evidence is currently sufficient to suggest that stress is a risk factor for the occurrence of periodontal disease in the presence of pathogens as well as the worsening of pre-existing periodontal diseases [8,12,15,17,[23][24][25][26].…”
Section: Progressive Establishment Of the Link Between Chronic Stressmentioning
confidence: 99%
“…In the case of a normal healing process, the production of cytokines, interleukins (IL-1b, IL-6, IL-8), and TNF-a decreased significantly. In a stressed subject with periodontitis, the production rate is high, resulting in an increase in the severity of periodontal damage [19]. Stress can also burden some aspects of the immune response such as mitogen stimulation, antibody and cytokine production, and NK cell activity [54].…”
Section: Blood Flow To the Gingivamentioning
confidence: 99%
See 1 more Smart Citation
“…7 Many studies have drawn attention to the role of the increase in local proinflammatory cytokine levels caused by these risk factors and their effects on the pathogenesis of periodontitis. 8,9 It has been reported that obesity, which is characterized by abnormal and excessive fat accumulation in the adipose tissue and has been shown to be one of the most important societal health problems today, affects the pathogenesis of periodontitis in a destructiveprovocative way. [10][11][12][13] Nishada et al 14 reported that obesity is the second most important risk determinant, following smoking, in the pathogenesis of inflammatory periodontal diseases.…”
Section: Introductionmentioning
confidence: 99%